Kebijakan Pengembangan Komoditas Tanaman Pangan dalam Mendukung Program Master Plan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI) Studi Kasus di Propinsi Gorontalo - Winarso, Bambang (Jurnal Penelitian Pertanian Terapan, 2013)
Master Plan for the Acceleration and expansion of Indonesia's Economic Development (MP3I) is one of economic development of the guidelines used by the government in its efforts to accelerating national development towards a just and prosperous society, especially in 2025. To realize this activities of the Government especially the Ministry of Agriculture has launched four main targets of agricultural development are: (1) realizing the achievement self-sufficiency and sustainable self-sufficiency, (2) achieve increased diversification, (3) realize an increase in value added, competitiveness, and exports, and (4) realize increased welfare of farmers. Food commodities is a strategic commodity, where compliance should always be available to the public. The issue of the need, availability and production of major food today. One of the corridors that are directed to the development of food commodities is Island Sulawesi as fourth corridor, which Gorontalo province is part of the Regions corridors. However, in the preparation and implementation of the field is still stout encountered obstacles and barriers. Lack of infrastructure, facilities and infrastructure that can support acceleration of growth seems to still be a problem that needs to be above. Keywords: Foodstuffs Commodity, MP3EI, Gorontalo